A Comparison of Endothelial Cell Loss in Combined Cataract and MIGS (Hydrus) Procedure to Phacoemulsification Alone: 6-Month Results. (17th November 2015) - Fea, Antonio M.; Consolandi, Giulia; Pignata, Giulia; Cannizzo, Paola Maria Loredana; Lavia, Carlo; Billia, Filippo; Rolle, Teresa; Grignolo, Federico M.
Abstract : Purpose . To compare the corneal endothelial cell loss after phacoemulsification, alone or combined with microinvasive glaucoma surgery (MIGS), in nonglaucomatous versus primary open angle glaucoma (POAG) eyes affected by age-related cataract. Methods . 62 eyes of 62 patients were divided into group 1 (n = 25, affected by age-related cataract) and group 2 (n = 37, affected by age-related cataract and POAG). All patients underwent cataract surgery. Group 2 was divided into subgroups A (n = 19, cataract surgery alone) and B (n = 18, cataract surgery and MIGS). Prior to and 6 months after surgery the patients' endothelium was studied. Main outcomes were CD (cell density), SD (standard deviation), CV (coefficient of variation), and 6A (hexagonality coefficient) variations after surgeries. Results . There were no significant differences among the groups concerning preoperative endothelial parameters. The differences in CD before and after surgery were significant in all groups: 9.1% in group 1, 17.24% in group 2A, and 11.71% in group 2B. All endothelial parameters did not significantly change after surgery. Conclusions . Phacoemulsification determined a loss of endothelial cells in all groups. After surgery the change in endothelial parameters after MIGS was comparable to the ones of patients who underwent cataract surgery alone.